2005
DOI: 10.1186/cc3026
|View full text |Cite
|
Sign up to set email alerts
|

Patients' recollections of experiences in the intensive care unit may affect their quality of life

Abstract: Introduction We wished to obtain the experiences felt by patients during their ICU stay using an original questionnaire and to correlate the memories of those experiences with health-related quality of life (HR-QOL). Methods We conducted a prospective study in 10 Portuguese intensive care units (ICUs). Six months after ICU discharge, an original questionnaire on experiences of patients during their ICU stay, the recollection questionnaire, was delivered. HR-QOL was evaluated simultaneously, with the EQ-5D ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(54 citation statements)
references
References 23 publications
2
47
1
4
Order By: Relevance
“…Thirty percent of participants in this study recalled being unable to let people know what they wanted, similar to findings by Rattray et al (2010). However this percentage is lower than reported in other studies in which 40 to 62% of patients reported communication as stressful or difficult (Granja et al, 2005; Happ et al, 2011; Patak et al, 2004). This discrepancy may in part be due to the wording of the communication item in the ICEQ that asks participants to rate how often they were able to let people know what they wanted, a measure of effectiveness of communication rather than the stress related to communication.…”
Section: Discussionsupporting
confidence: 80%
“…Thirty percent of participants in this study recalled being unable to let people know what they wanted, similar to findings by Rattray et al (2010). However this percentage is lower than reported in other studies in which 40 to 62% of patients reported communication as stressful or difficult (Granja et al, 2005; Happ et al, 2011; Patak et al, 2004). This discrepancy may in part be due to the wording of the communication item in the ICEQ that asks participants to rate how often they were able to let people know what they wanted, a measure of effectiveness of communication rather than the stress related to communication.…”
Section: Discussionsupporting
confidence: 80%
“…Pain is highly underestimated although it seems to be the patients’ worst memory in intensive care unit (ICU) [1, 2] even after 5 years from ICU discharge [3]. The perception of pain in ICU patients is mainly associated with respiratory therapy, positioning of nasogastric tube, venous and arterial catheters, and lack of mobilization [2].…”
Section: Introductionmentioning
confidence: 99%
“…Our research team reviewed existing questionnaires for distress in critical care [8-10], but found none were suitable as a quick screening tool. Existing questionnaires were too long, contained many items not relevant to this purpose, or were primarily measures of post-critical care recall rather than current experience of critical care.…”
Section: Introductionmentioning
confidence: 99%